Organic Semiconductors - Alvarado Rivera, Josefina (Springer Nature Switzerland, 2019)
One of the most exciting opportunities in electronics, optoelectronics or flexible electronics is to be able to make devices based on organic semiconductors. Organic active materials can exhibit many advantages such as lower demands on processing technology with less sensitivity to the processing environment, flexibility, and the opportunity to apply the simplicity of organic synthesis to tailoring the properties of the materials for specific applications [1]. Depending on their vapor pressure and solubility, organic semiconductors are deposited either from a vapor or solution phase. In this section, some of the organic semiconductor deposition methods are discussed. Similar to its inorganic counterparts, organic semiconductors have been the subject of extensive research to produce organic electronic devices such as organic photovoltaic cells (OPV), organic field-effect transistors (OFET), and organic lightemitting diodes (OLED) [2, 3, 73–77, 82]. However, organic semiconductors have certain limitations such as a short lifetime, degradation byUVlight, temperature sensitivity, low efficiency compared to inorganic semiconductors, and not well understood charge transfer mechanisms. Despite these limitations, advantages like their lightweight, transparency, flexibility, and lower production cost make them candidates for the development of novel electronic devices fomenting research in this area. It is worthwhile to note that organic semiconductors have been combined with other carbon nanomaterials like carbon nanotubes, fullerenes, and graphene, to improve their charge carrier mobility, which is one of the limitations of polymers and oligomers.